Brazilian version of the Hammersmith Functional Motor Scale Expanded: cross-cultural adaptation and validation - Moura, Ana Carolina Monteiro Lessa de; Carvalhais, Marina Belisário; Sampaio, Gabriela Palhares Campolina; Pinhati, Clara Catharino; Montes, Jacqueline; Gurgel-Giannetti, Juliana (Arquivos de Neuro-Psiquiatria, 2024)
Background The Hammersmith Functional Motor Scale Expanded (HFMSE) has been widely used to assess the motor function of patients with spinal muscular atrophy (SMA) older than 2 years, with the ability to sit and/or walk.Objective To translate, cross-culturally adapt and validate the HFMSE to Brazilian Portuguese.Methods The translation process and cross-cultural adaptation followed international guidelines recommendations. The reliability and applicability of the Brazilian version consisted of the application of the HFMSE (in Brazilian Portuguese) to 20 patients with types 2 and 3 SMA. Two examiners assessed the participants for interrater reliability, through the analysis of Kappa reliability agreement (k) and intraclass correlation coefficient (ICC).Results The HFMSE was successfully translated and cross culturally adapted to Brazilian Portuguese. Twenty participants with types 2 and 3 SMA were enrolled in the study (type 2 = 6; type 3 = 14). The ICC for the total score showed very high reliability (ICC =1.00), and the reliability of each of the items individually was considered excellent (Kappa > 0.80).Conclusion The Brazilian version of the HFMSE proved to be valid and reliable for the evaluation of SMA patients older than 2 years with the ability to sit and/or walk.
Keywords: Motor Activity; Muscular Atrophy, Spinal; Validation Study